PENGARUH IMPLEMENTASI PERATURAN BUPATI NOMOR 18 TAHUN 2011 TERHADAP PENINGKATAN DISIPLIN KERJA PEGAWAI (STUDY KASUS BADAN PERENCANAAN PEMBANGUNAN DAERAH DAN SEKRETARIAT DAERAH KABUPATEN ROKAN HULU) - Padia Amri; Sujianto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Discipline is a starting point of all success in order to achieve the objectives of the organization. Therefore, the local goverment in the districks Rokan Hulu make regulation regent No. 18 of 2011 on compolsory prayer noon dan asr in congregation at mosques Pasir Pangarayan for Muslim employee in the working day in the administration districts Rokan Hulu in order to increase the devotion of empliyess to god almight one that affects discipline increase employeyment. Planning and regional Development Agencies Rokan hulu and Rokan Hulu Secretariat upstream part of the governance environment districts Rokan Hulu.This study aims to determine the implementation of the decree no. 18 of 2011. Dicipline of employess working in really in development Planning and Rokan Hulu Regency Secretariat inflence the implementation mainly Regent No. 18 of 2011 to dicipline the local Planning Agancy and the regional Secretariat Rokan Hulu.In this study the typies of research used in quantitative research required data collected to the study site with the questionnaire in this study are emplyess of the local palnning agancy Rokan Hulu 55 and Rokan Hulu district Secretariat asmany as 119 people.As this study using a Likert scale ewrw analized using simple Linier regression analysis and determination with the help of SPSS version 17.0 for Windows.The results of this study indicate that the implemantation of the decree No. 18 of 2011 against increased employee discipline Development planning Rokan Hulu great influence 23% and Rokan Hulu district Secretariat a big influence 29%.Key Words : Implementation, Dicipline